Otimização do pré-tratamento das ramas de batata-doce (Ipomoea batatas lam. (l)) utilizando ácido sulfúrico diluído - Barbosa, Robson dos Santos (Universidade Federal do Tocantins, 2020)
The production technologies for second-generation ethanol has great sustainable potential because they can reduce the impact of biomass that are discarded as waste in the environment and they can also provide the best use of first-generation ethanol crops than the current one. To make second generation ethanol production feasible the critical step is the pre-treatment, which improve enzymes accessibility in cellulose matrix, thus increasing process efficiency, and free sugars, reducing the enzymes loading. Therefore, this study aimed to optimize the conditions of dilute acid pretreatment of sweet potato foliage. To develop the experiment was used a central composite design with four factors: temperature (60 ° to 120 °), time (30 to 90 minutes), solids loading (2% to 10%) and acid concentration (1% to 5%). The response variables were the concentrations of monomers (glucose, xylose and arabinose) and inhibitors (HMF, furfural) in the hydrolysate. In more severe conditions it was possible to obtain 100% yield to arabinose, 38.46% to glucose and 63% to xylose, with negligible formation of inhibitors. The optimum operating conditions for the experiment were set to 105 ° C, 75 minutes process time, 8% solids loading, and concentration of 4% acid sulfuric, these conditions result in a release of 12,63g/l of glucose, 5, 01 g/l of xylose, 3,63 g/l of arabinose, 0,17 g/l of furfural and 0.29 g/l of HMF.